HUBUNGAN ANTARA DUKUNGAN KELUARGA DENGAN TINGKAT KECEMASAN PADA MAHASISWA YANG MENGERJAKAN SKRIPSI DI PROGRAM STUDI ILMU KEPERAWATAN UNIVERSITAS TRIBHUWANA TUNGGADEWI MALANG - Lasri Lasri; Kartika Ratih Pratiwi (Care : Jurnal Ilmiah Ilmu Kesehatan, 2014)
The anxiety is very disturbing homeostasis and the function of individual, because it needs to be removed with the various ways of adjustment. When the students experience the anxiety in the thesis working, support is useful to face the anxiety. The purpose of this study is to analyze the relationship between family support with the level of anxiety of students who worked the thesis in Nursing Science Program, University of Tribhuwana Tunggadewi Malang Year 2009. This study uses a correlational research design with cross sectional method. With total of sample 30 people that were taken by Simple Random Sampling. Instrument used was a questionnaire. The collection data were analyzed using Spearman's rho test with α = 0.05. From the result of study was obtained that most of respondents have a good family support with a number 19 people (63.3%), the anxiety level of most respondents is the medium anxiety level with a number 17 people (56.7%). The result of analysis shows the value of Sig. 2 tailed 0.000 < α 0.05 and Correlation Coefficient 0.809, so there is a very strong relationship between the family support with the levels of anxiety. It si recommended to establish the educational guidance, support and motivation so the students do not experience the excessive anxiety when worked the thesis.